Human factors for engineers - Sandom, Carl; Harvey, Roger S. (London, United Kingdom Institution of Engineering and Technology, 2004)
The books reviews developments in the following fields: human factors; cost benefits; task analysis; risk assessment; control room design; human-computer interface; usability; and safety assessment.
Electronic reproduction.
Keywords: Human engineering; Electronic books